Ice nucleation proteins self-assemble into large fibres to trigger freezing at near 0 °C - Thomas Hansen; Jocelyn Lee; Naama Reicher; Gil Ovadia; Shuaiqi Guo; Wangbiao Guo; Jun Liu; Ido Braslavsky; Yinon Rudich; Peter L Davies (eLife, 2023)
In nature, frost can form at a few degrees below 0 °C. However, this process requires the assembly of tens of thousands of ice-like water molecules that align together to initiate freezing at these relatively high temperatures. Water ordering on this scale is mediated by the ice nucleation proteins (INPs) of common environmental bacteria like Pseudomonas syringae and Pseudomonas borealis. However, individually, these 100 kDa proteins are too small to organize enough water molecules for frost formation, and it is not known how giant, megadalton-sized multimers, which are crucial for ice nucleation at high sub-zero temperatures, form. The ability of multimers to self-assemble was suggested when the transfer of an INP gene into Escherichia coli led to efficient ice nucleation. Here, we demonstrate that a positively charged subdomain at the C-terminal end of the central β-solenoid of the INP is crucial for multimerization. Truncation, relocation, or change of the charge of this subdomain caused a catastrophic loss of ice nucleation ability. Cryo-electron tomography of the recombinant E. coli showed that the INP multimers form fibres that are ~5 nm across and up to 200 nm long. A model of these fibres as an overlapping series of antiparallel dimers can account for all their known properties and suggests a route to making cell-free ice nucleators for biotechnological applications.